Factors associated with capacities development in learning physic associate on numerical systems and Hamming code (2020)
the research uses mixed, participatory action research tools within qualitative research, and factor analysis from the positivist approach; identifies and analyses factors associated with problem solving in capacity development within the framework of the metacognitive in learning of the physic, associate to approach with operations of numerical systems and detection error with Hamming code, is apply in the childhood of public educational institutions located in the border area of the Municipality of Villa del Rosario, Colombia. For this purpose, a diagnostic test was applied (α = 0.78), which allowed the identification of difficulties and variables related to learning and application in real contexts (r = 0.81); and a post-test (K = 0.7), that evaluates projects as a didactic strategy. There was evidence of the construction of knowledge and the application of these to practical life, also revealed that it was possible to awaken interest and motivation in students which significantly improved their level of analysis, interpretation and reasoning. Associated factors were coexistence (α = 0.788), emotional proposal didactics (α = 0.751), metacognitive skills (α = 0.767), self-control (α = 0.718), evaluation (α = 0.712), strategies and abilities in physic through the method and its application in logical circuits with indicators cognitive, attitudinal, motor processes.